Exploring the Intersection of Game-Based Learning and Sustainable Education in Engineering: A Bibliometric Analysis - Uzeda, Luiz Eduardo; Parreiras, Marcus; Xexéo, Geraldo (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
This study conducts a bibliometric analysis on the use of Sustainable Game-Based Learning in Higher Education in Engineering. Research reveals growing interest in this field, with a progressive increase in publications over the years. It also determined the journals that publish the most frequently on the topic and the most frequently used keywords. Our findings indicate that the intersection of games, sustainability, and education is being explored as an effective pedagogical strategy in higher education in Engineering.